Resolusi Komunikasi Konflik Antarsuporter Sepak Bola di Instagram Viking Persib Club - Kelvin Wahana Putra; Indriyati Kamil; Rezsa Yushardiansyah (GLOBAL SCIENTS PUBLISHER, 2026)
Conflicts between football supporters in Indonesia manifest not only as physical clashes but also play out on social media through the spread of hate speech, provocations, and information that can exacerbate tensions between supporter groups. Conversely, social media can serve as a communication tool to foster peace and support conflict resolution efforts. This study aims to analyze the role of the Viking Persib Club Instagram account in supporting conflict resolution among football supporters. A qualitative method with a case study approach was employed. Data were gathered through observations of the @officialvpc Instagram account's posts, in-depth interviews with the club's media administrators and members, and documentation. Data analysis involved reduction, presentation, and conclusion drawing, utilizing Lewis A. Coser’s conflict theory—specifically the concepts of realistic conflict, non-realistic conflict, in-group conflict, and out-group conflict. The findings indicate that the Viking Persib Club Instagram account is utilized to clarify information, campaign for peace, educate on social media ethics, and strengthen solidarity among supporters. In realistic conflict scenarios, Instagram serves as a channel for official information to minimize misunderstandings and prevent escalation. Regarding non-realistic conflict, the platform is used to counter provocation and hate speech by promoting narratives of sportsmanship and brotherhood. Meanwhile, in the context of in-group and out-group conflicts, Instagram plays a role in reinforcing internal solidarity while fostering more positive relationships with other supporter groups. The study concludes that social media functions not merely as a channel for disseminating information but also as a strategic communication instrument for supporting conflict resolution and promoting peaceful communication within the football supporter community.